Plausible legality legal culture and political imperative in the global war on terror - Sanders, Rebecca 1975- (Oxford studies in culture and politics, 2018)
After 9/11, American officials authorized numerous contentious counterterrorism practices including torture, extraordinary rendition, indefinite detention, trial by military commission, targeted killing, and mass surveillance. While these policies sparked global outrage, the Bush administration defended them as legally legitimate. Government lawyers produced memoranda deeming enhanced interrogation techniques, denial of habeas corpus, drone strikes, and warrantless wiretapping lawful. Although it rejected torture, the Obama administration made similar claims and declined to prosecute abuses. This work seeks to understand how and why Americans repeatedly legally justified seemingly illegal security policies and what this tells us about the capacity of law to constrain state violence